EDUCATION 5.0: COLLABORATION AND CREATIVITY IN IMPROVING STUDENTS' DIGITAL INTELLIGENCE - Loso Judijanto; La Ili; Megandhi Gusti Wardhana (International Journal of Teaching and Learning, 2025)
Education 5.0 is an innovative approach to education that integrates advanced technology and the latest learning methodologies to create a student-centred learning environment. The research method conducted in this study is literature. The results showed that students' digital intelligence, creativity, and collaborative skills improved. The implementation of Education 5.0, which embraces technology and innovative learning methodologies, facilitates a more dynamic and interactive learning environment, increasing student motivation and participation in the learning process. Study results indicated students engaged in an Education 5.0- based curriculum showed improved performance in complex problem solving, critical thinking, and teamwork, compared to traditional approaches. Furthermore, the findings suggest that educators, as facilitators, play a key role in inspiring student innovation and creativity through the use of technology and project-based learning approaches. The implementation of Education 5.0 not only enriches students' learning experiences but also prepares them with relevant skills for future challenges, underscoring the importance of transitioning to a more flexible and adaptive educational paradigm in preparing students for success in an ever-changing global society.